AKTOR PEMBENTUK JARINGAN PESANTREN DI SULAWESI SELATAN 1928-1952 - Syamsuddin Arief (Faculty of Tarbiyah and Teacher Training Universitas Islam Negeri Alauddin Makassar, 2007)
Anre Gurutta Haji (A.G.H) Muhammad As’ad is one of the actors of forming Islamic Boarding Schools in South Sulawesi. He went back from Makkah and went to Sengkang-Wajo in 1928. He graduated from al-Falah Makkah Mukarramah. He studied to the great Ulamas in the Mesjidil Haram (Haram Mosque). Among of his teachers were Syekh Abdul Rasyid al-Bugis, Syekh Ambo Wellang al-Bugis, Syekh Abbas Abdul Jabbar al-Bugis, Syekh Mallawa al-Bugis, Syekh Umar Hamdani (the traditional expert), Syekh Ahmad Azdirin, Syekh Jamal Makki, Syekh al-Abrar, Syekh Muhammad Said al-Yamani, and Syekh Hasan al-Yamani. Another students of A.G.H Muhammad As’ad who helped as teachers such as A.G.H Abdurrah-man Ambo Dalle, A.G.H Daud Ismail, A.G.H Yunus Maratn, Hamzah Badawi, Abdul Malik Muhammad, A.G.H Muhammad Abduh Pabbaja, Abdul Muin Yusuf, and Abdul Azis (North Luwu).